Vertebral canal morphology as assesed from radiometric examinations - Zaborowski, Zbigniew (Anthropological Review, 1976)
On X-ray pictures width and depth of the vertebral canal were measured in 200 individuals of both sexes. The material has been broken down into 7 age groups: 0 1 weeks, 1, 3, 7 years, 11-13, 16-18 and 22-26 years. Metrical data were eleborated with standard statistical techniques. It has been shown that in newborns some characteristics of the canal are similar to those in adults, especially with regard to canal width. The greatest growth dynamics of the canal is observed during first year of life, in next years the dynamics seriously decreases. At the begining of adolescence the canal attains dimensions not essentially different from ultimate, typical for adults. Termination of canals growth occurs at the end of adolescence. In the growth of vertebral canal, so typical for other characters of vertebral column, growth spurts were not found.